Factors Influencing Likelihood of Voice Therapy Attendance: Report from the CHEER Network. (March 2017) - Misono, Stephanie; Marmor, Schelomo; Roy, Nelson; Mau, Ted; Cohen, Seth M.
Objective: To identify factors associated with the likelihood of attending voice therapy among patients referred for it in the CHEER (Creating Healthcare Excellence through Education and Research) practice-based research network infrastructure. Study Design: Prospectively enrolled cross-sectional study. Setting: CHEER network of community and academic sites. Methods: Data were collected on patient-reported demographics, voice-related diagnoses, voice-related handicap (Voice Handicap Index–10), likelihood of attending voice therapy (VT), and opinions on factors influencing likelihood of attending VT. The relationships between patient characteristics/opinions and likelihood of attending VT were investigated. Results: A total of 170 patients with various voice-related diagnoses reported receiving a recommendation for VT. Of those, 85% indicated that they were likely to attend it, regardless of voice-related handicap severity. The most common factors influencing likelihood of VT attendance were insurance/copay, relief that it was not cancer, and travel. Those who were not likely to attend VT identified, as important factors, unclear potential improvement, not understanding the purpose of therapy, and concern that it would be too hard. In multivariate analysis, factors associated with greater likelihood of attending VT included shorter travel distance, age (40-59 years), and being seen in an academic practice. Conclusions: Most patients reported plans to attend VT as recommended. Patients who intended to attend VT reported different considerations in their decision making from those who did not plan to attend. These findings may inform patient counseling and efforts to increase access to voice care.